2007
DOI: 10.1152/ajpendo.00241.2006
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure adjusted for body composition differentiates constitutional thinness from both normal subjects and anorexia nervosa

Abstract: Constitutional thinness (CT) is characterized by a low and stable body mass index (BMI) without any hormonal abnormality. To understand the weight steadiness, energetic metabolism was evaluated. Seven CT, seven controls, and six anorexia nervosa (AN) young women were compared. CT and AN had a BMI <16.5 kg/m(2). Four criteria were evaluated: 1) energy balance including diet record, resting metabolic rate (RMR) (indirect calorimetry), total energy expenditure (TEE) (doubly labeled water), physical activity; 2) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(124 citation statements)
references
References 42 publications
(41 reference statements)
6
116
0
1
Order By: Relevance
“…Few data have so far been reported on body composition in constitutionally lean patients and underweight dancers, indicating just a reduction in body fat (Young et al, 1994;Eliakim et al, 2000;Yannakoulia et al, 2000;Scalfi et al, 2001;Matthews et al, 2006;Bossu et al, 2007). The results of this study show that subcutaneous skinfolds and the percentage of body fat between the three groups of underweight patients (who had similar BMI) were largely comparable and that no differences emerged due to chronic underfeeding (anorectic patients) or regular physical exercise (dancers).…”
Section: Discussionmentioning
confidence: 48%
“…Few data have so far been reported on body composition in constitutionally lean patients and underweight dancers, indicating just a reduction in body fat (Young et al, 1994;Eliakim et al, 2000;Yannakoulia et al, 2000;Scalfi et al, 2001;Matthews et al, 2006;Bossu et al, 2007). The results of this study show that subcutaneous skinfolds and the percentage of body fat between the three groups of underweight patients (who had similar BMI) were largely comparable and that no differences emerged due to chronic underfeeding (anorectic patients) or regular physical exercise (dancers).…”
Section: Discussionmentioning
confidence: 48%
“…Ghrelin was higher among AN women while leptin levels were significantly lower. Similarly, another small study of seven constitutionally thin women, seven normal controls, and six patients with restricting subtype AN (AN-R) 12 found that AN patients consumed a significantly smaller percentage of lipids and had significantly less fat mass percentage though the groups had comparable total energy expenditure. Women with AN also had significantly lower free thyroid hormone T3, IGF-1 and leptin when compared with normal controls and constitutionally thin women.…”
Section: Potential Biological Differences Signified By Amenorrheamentioning
confidence: 91%
“…Inclusion criteria were as follows: BMI between 12.0 and 16.5 kg/m 2 , called "severe underweight" according to the World Health Organization classification (15), stable throughout the growth period until the age of 18 (14); presence of physiological menstruation without estrogen-progestin therapy; and desire for weight gain as the main reason for medical consultation.…”
Section: Subjectsmentioning
confidence: 99%
“…These young women are severely thin but continue to have a close-to-normal FM percentage, normal physiological menstrual cycles, and no detectable abnormalities of cortisol, IGF-I, or free T 3 secretory patterns (13), and normal energy metabolism (14). In this context, we wanted to determine whether constitutional thinness could still represent a phenotype of impaired bone quality, in terms of bone mass, bone macroarchitecture and microarchitecture, and bone turnover.…”
mentioning
confidence: 99%